The delivery modes and morbidity/mortality in very preterm infants with birth weight <1,500 g: a retrospective cohort study - Wang, Haoran; Xu, Xiaoming; Zhang, Meng; He, Yang (Frontiers in Public Health, 2025)
IntroductionCompare outcomes of very preterm infants (VPIs) with a birth weight<1,500 g based on delivery mode and propensity score matching (PSM).MethodsThis was a retrospective study (2016–2021) of 1,375 VPIs (692 vaginal and 683 cesarean deliveries). PSM created 390 matched pairs. Outcomes included respiratory and neurological morbidity and mortality.ResultsPSM revealed no significant difference between the two groups at baseline or after antenatal corticosteroids administration. The incidence rates of birth asphyxia, delivery room resuscitation, neonatal respiratory distress syndrome, use of pulmonary surfactants, pulmonary hemorrhage, and use of invasive ventilation in the vaginal delivery group after PSM were 42.3, 68.2, 65.9, 59.2, 7.2, and 36.7%, respectively. These rates were significantly lower than those in the cesarean delivery group (52.3, 83.3, 79.5, 70.8, 14.4, and 51.8%, respectively) (p < 0.05). The difference was more significant in infants with a gestational age of 28–31+6 weeks (p < 0.05). There were no significant differences in the incidence rates of intraventricular hemorrhage (IVH), severe IVH, periventricular leukomalacia, bronchopulmonary dysplasia, necrotizing enterocolitis (NEC), NEC surgery, premature infant retinopathy (ROP), severe ROP, late-onset neonatal sepsis, or mortality between the two groups. The mortality rate within 3 days in the vaginal delivery group was 7.7%, which was higher than that in the cesarean delivery group (3.3%), primarily in infants with a gestational age < 28 weeks (p < 0.05).ConclusionCesarean section reduced early mortality in VPIs <28 weeks but increased respiratory morbidity at 28–31+6 weeks, with no impact on other outcomes. Since 52.1% of the cesarean sections were emergency procedures, this may have biased the results.